Variations in the Detection of Anorectal Anomalies at Birth among European Cities - Aldeiri, Bashar; Davidson, Joseph R.; Eaton, Simon; Coletta, Riccardo; Cardoso Almeida, Andre; Long, Anna-May; Knight, Marian; Cross, Kate M.; Chouikh, Taieb; Iacobelli, Barbara Daniela; Sarnacki, Sabine; Bagolan, Pietro; Cretolle, Celia; Siminas, Sotirios; Curry, Joe I.; Morabito, Antonino; De Coppi, Paolo (European Journal of Pediatric Surgery, 2020)
Introduction The diagnosis of anorectal malformations (ARMs) is made at birth by perineal examination of the newborn, yet small series reported late diagnosis in almost 13%. No large series to date have looked into the magnitude of missed ARM cases in the neonatal period across Europe. This study aimed to define the rate of missed ARM at birth across four United Kingdom and European Union centers.Materials and Methods All ARM cases treated at two United Kingdom tertiary centers in the past 15 years were compared with two tertiary European centers. Demographic and relevant clinical data were collected. Late diagnosis was defined as any diagnosis made after discharge from the birth unit. Factors associated with late diagnosis were explored with descriptive statistics.Results Across the four centers, 117/1,350, 8.7% were sent home from the birth unit without recognizing the anorectal anomaly. Missed cases showed a slight female predominance (1.3:1), and the majority (113/117, 96.5%) were of the low anomaly with a fistula to the perineum. The rate of missed ARM cases was significantly higher in the United Kingdom centers combined (74/415, 17.8%) compared with those in the European Union (43/935, 4.6%) (p < 0.00001), and this was independent of individual center and year of birth.Conclusion Significant variation exists between the United Kingdom and other European countries in the detection of ARM at birth. We recommend raising the awareness of accurate perineal examination at the time of newborn physical examination. We feel this highlights an urgent need for a national initiative to assess and address the timely diagnosis of ARM in the United Kingdom.
Keywords: anorectal malformations; congenital anomaly; postnatal checks; pediatric surgery